Bioresorbable Microspheres with Surface‐Loaded Nanosilver and Apatite as Dual‐Functional Injectable Cell Carriers for Bone Regeneration. Issue 20 (11th May 2018) - Wei, Pengfei; Yuan, Zuoying; Cai, Qing; Mao, Jianping; Yang, Xiaoping
Abstract: Bone defect repair, especially in terms of infection, remains a big challenge in clinical therapy. To meet clinical requirements, the dual‐functional strategy including antibacterial activity and strong osteogenesis effect is a promising approach in bone tissue engineering. In the present study, bioresorbable porous‐structured microspheres are fabricated from amphiphilic block copolymer composed of poly(l ‐lactide) and poly(ethyl glycol) blocks. After being surface coated with mussel‐inspired polydopamine, the microspheres are loaded with nanosilver via reduction of silver nitrate and apatite via biomineralization in sequence. The resulting composite microspheres are systematically characterized by in vitro coculturing with rat bone mesenchymal stromal cells and Staphylococcus aureus to evaluate cytotoxicity and antibacterial activity. In vivo evaluation is carried out by filling the composite microspheres into infected cranial defects in a rat model. The primary results indicate that the dual‐purpose microspheres have the capacity to defeat infection while promoting bone regeneration. Abstract : Dual‐functional porous microspheres with both antibacterial activity and osteocompatibility, which are injectable and bioresorbable, are found to be effective and efficient in treating infected bone defects to induce bone regeneration.